Effects of inappropriate cause-of-death certification on mortality from cardiovascular disease and diabetes mellitus in Tonga - Carah A. Figueroa; Christine L. Linhart; Catherine Dearie; Latu E. Fusimalohi; Sioape Kupu; Stephen L. Morrell; Richard J. Taylor (BMC, 2023)
Abstract Background Cardiovascular disease (CVD) and diabetes mellitus are major health issues in Tonga and other Pacific countries, although mortality levels and trends are unclear. We assess the impacts of cause-of-death certification on coding of CVD and diabetes as underlying causes of death (UCoD). Methods Tongan records containing cause-of-death data (2001-2018), including medical certificates of cause-of-death (MCCD), had UCoD assigned according to International Classification of Diseases 10th revision (ICD-10) coding rules. Deaths without recorded cause were included to ascertain total mortality. Diabetes and hypertension causes were reallocated from Part 1 of the MCCD (direct cause) to Part 2 (contributory cause) if potentially fatal complications were not recorded, and an alternative UCoD was assigned. Proportional mortality by cause based on the alternative UCoD were applied to total deaths then mortality rates calculated by age and sex using census/intercensal population estimates. CVD and diabetes mortality rates for unaltered and alternative UCoD were compared using Poisson regression. Results Over 2001-18, in ages 35-59 years, alternative CVD mortality was higher than unaltered CVD mortality in men (p = 0.043) and women (p = 0.15); for 2010-18, alternative versus unaltered measures in men were 3.3/103 (95%CI: 3.0-3.7/103) versus 2.9/103 (95%CI: 2.6-3.2/103), and in women were 1.1/103 (95%CI: 0.9-1.3/103) versus 0.9/103 (95%CI: 0.8-1.1/103). Conversely, alternative diabetes mortality rates were significantly lower than the unaltered rates over 2001-18 in men (p < 0.0001) and women (p = 0.013); for 2010-18, these measures in men were 1.3/103 (95%CI: 1.1-1.5/103) versus 1.9/103 (95%CI: 1.6-2.2/103), and in women were 1.4/103 (95%CI: 1.2-1.7/103) versus 1.7/103 (95%CI: 1.5-2.0/103). Diabetes mortality rates increased significantly over 2001-18 in men (unaltered: p < 0.0001; alternative: p = 0.0007) and increased overall in women (unaltered: p = 0.0015; alternative: p = 0.014). Conclusions Diabetes reporting in Part 1 of the MCCD, without potentially fatal diabetes complications, has led to over-estimation of diabetes, and under-estimation of CVD, as UCoD in Tonga. This indicates the importance of controlling various modifiable risks for atherosclerotic CVD (including stroke) including hypertension, tobacco use, and saturated fat intake, besides obesity and diabetes. Accurate certification of diabetes as a direct cause of death (Part 1) or contributory factor (Part 2) is needed to ensure that valid UCoD are assigned. Examination of multiple cause-of-death data can improve understanding of the underlying causes of premature mortality to better inform health planning.